Prediksi Kebangkrutan Perusahaan Berdasarkan Analisa Model Z-Score Altman Studi Kasus Pada Pt. Telekomunikasi Selular (Telkomsel) - Andoko, Andoko (Universitas Pelita Harapan Medan, 2021)
This study was conducted to determine whether the PT. Telkomsel Tbk. predicted to be bankrupt according to Z-score model analysis of the 2010-2012 annual report. Population of this research consists of 7 companies, namely: 6 companies listed on the Stock Exchange add up with PT. Telkomsel Tbk., with 6 companies taken as sample by purposive sampling method Data used in this study is secondary data in the form of financial statements of each sample, which is published in www.telkomsel.com , www.bakrietelecom.com , www.indosat.com , www.inovisi.com , www.smartfren.com , www.xl.co.id , and www.idx.co.id. Independent variables used are Working Capital to Total Assets Ratio (X1), Retained Earnings to Total Assets Ratio (X2), Earnings Before Interest and Taxes to Total Assets Ratio (X3), Book Value Equity to Book Value of Total Liabilities Ratio (X4), with the value of the Z-Score as the dependent variable. Analysis technique that is being used is Altman Z-Score analysis, descriptive statistics as well as the Mann Whitney test. The analysis of the Altman Z-Score to PT. Telkomsel Tbk., shows Z-Score value of 4.557 in 2010, 5.581 in 2011, and 6.899 in 2012, so PT. Telkomsel Tbk. is within the safe zone because the Z - Score value is greater than 2.60. Based on the Mann Whitney test, shows that the PT. Telkomsel Tbk. have significant differences in the value of the Z-Score with PT. Bakrie Telecom Tbk. (Z-Score year 2012-2010 = -0.044; 2.297; 3.783), PT. Indosat Tbk. (Z-Score year 2012-2010 = 4.714; 4.442; 4.372), PT. Smartfren Telecom Tbk. (Z-Score year 2012-2010 = 0.251; -0.511; -3.373), PT. XL Axiata Tbk. (Z-Score in 2012-2010 = 4,837; 4,734; 5.406), whereas PT. Infracom Tbk. (Z-Score year 2012-2010 = 11.298; 8.902; 8.857) had no significant difference in the value of the Z-score with PT. Telkomsel Tbk. The financial condition of PT. Telkomsel Tbk. relatively better than other telecom companies listed on the Stock Exchange from 2010-2012.Keywords : Z-Score, bankruptcy prediction